Three new species of the genus Choeras Mason, 1981 (Hymenoptera: Braconidae, Microgastrinae) from Iran - Abdoli, Parisa; Talebi, Ali Asghar; Farahani, Samira; Fernandez-Triana, Jose (Zootaxa, 2019)
The genus Choeras Mason, 1981 (Hymenoptera: Braconidae, Microgastrinae) in northern Iran is studied taxonomically. Specimens were collected using Malaise traps during 2010 and 2011. A total of five species were identified, three being new species which are described and illustrated: Choeras formosus Abdoli & Fernandez-Triana sp. nov., C. fulviventris Fernandez-Triana & Abdoli sp. nov. and C. qazviniensis Fernandez-Triana & Talebi sp. nov. Two species (i.e., C. taftanensis and C. tiro) are new provincial records. The number of Choeras species in Iran is now raised to seven. An identification key to all West Palaearctic species of Choeras is provided.